Opinion of handball players, trainers and referees using the handball/futsal goalpost anti-tip system "Tutigool" for a safe game: 2019 Four Nations International Handball Junior Tournament - Baena-Gonzalez, R.; Garcia-Tascon, M.; Chavarria-Ortiz, C.; Martinez-Martin, I.; Gallardo, A. M. (Journal of Physical Education and Sport, 2020)
Problem Statement:Athletes and especially children die around the world due to sports accidents. In this regard, changes in the federal sports regulations are not only aimed at favoring the game, but also to improve the safety of athletes. In handball, the goal is an essential piece of equipment and the anti-tip system used is fundamental to prevent accidents. Purpose:The objective of the present study was to know the opinion of different sports agents about the use of the Tutigool anti-tip system in the goals. Methods:The sample consisted of 60 subjects (players (51 ± 0.72), trainers (5 ± 14.01), and referees (4 ± 2.5)), of which, 96.7% were men and 3.3% women. Amodified Likert-scale questionnaire was filled out (1 = strongly disagree to 7 = strongly agree) by the participants of the Four Nations International Tournament in January 2019 in the male U21 category, held in Santander (Spain). The questionnaire consisted of 18 items. Results: The most relevant results affirm that the system is appropriate for the handball game at the municipal and school level at 5.35 and for high level sports at 4.10. The average satisfaction with this system is 4.34. By agents, the coaches obtained 5.4, the referees 4.5 and the players 4.22. The Kruskal-Wallis test was carried out, which showed no significant differences in the mean scores (p> 0.05) given by players, trainers and referees in different aspects related to the anti-tip system. Conclusions:These results allow making a deep reflection and a change in handball regulations with the aim of adapting them and guaranteeing a safer practice, not only for athletes and amateur users, but also for sports facilities technicians who are responsible for the maintenance and handling of sports equipment.